Culturas urbanas: simbologias e significados - Aranha, Alexandre Alves (2013)
The city of Curitiba has inserted itself into a cultural aspects of which were built over transformations which crossed the city. These changes in Curitiba are the starting point for this study, which adhered to observe urban cultures established by curitibanos. These different cultural expressions building codes and rules, which give meanings to certain areas of the city. Thus, boundaries are created, is often not practical, however, that indicate boundaries forms of control and contention. This text also addresses the narrative about elected by curitibanos spaces, as places of religious cultural practices. Analysis of these places, demonstrating the importance of a territory to the consolidation of religious practices. In this respect, the paper addresses some of these places used for worship, as places of sociability, where the symbols along with their meanings, are socialized by their patrons. In this vein, the text aims to establish a narrative about religion and religious popular culture, demonstrating different forms of devotional practices of Curitiba, locations and characters grounded in elected and constructed by urban culture of Curitiba.